The relationship between childhood trauma and post-traumatic growth among college students: The role of acceptance and positive reappraisal - Quan, Lijuan; Lü, Bijun; Sun, Jialei; Zhao, Xintong; Sang, Qingsong (Frontiers in Psychology, 2022)
Objective To examine the relationship among childhood trauma, acceptance, positive reappraisal and post-traumatic growth (PTG) among college students. Methods Research participants were selected by random cluster sampling. 1,028 college students (62.6% female, 30.5% only-children) from 8 universities were investigated using manuscript-pencil survey versions of Childhood Trauma Questionnaire-Short Form (CTQ-SF), Cognitive emotion regulation questionnaire–Chinese version (CERQ-C) and Post traumatic Growth Inventory (PTGI). Results Traumatic childhood experience significantly negatively predicts post traumatic growth in college students. Exposure to traumatic experiences in childhood can directly negatively predict post-traumatic growth and indirectly positively predict post traumatic growth via acceptance. Conclusion Acceptance plays a mediating role between childhood traumatic experience and post traumatic growth. The mediating effect of acceptance is moderated by the positive reappraisal. When individuals have a lower level of positive reappraisal, the mediating effect between traumatic experience and post traumatic growth is significant. Several clinical implications for clinical psychology and psychological intervention are highlighted. Starting with changing individual cognition and helping individuals adopt positive cognitive emotion regulation strategies can help individuals actively reevaluate traumatic experience, so as to gain better and faster counseling results.